London's River? The Thames as Contested Environmental Space. (November 2015) - Taylor, Vanessa
Abstract : This introduction places the authors' contributions in the context of changes and recurring tensions across the period from 1960 to today. It reviews relevant literature and includes a brief overview of policy and political debates relating to the Thames during this period.